Creep behaviour of cemented carbides — Influence of binder content, binder composition and WC grain size. (January 2017) - Useldinger, R.; Schleinkofer, U.
Abstract: The high-temperature creep behaviour of cemented carbides was evaluated for a wide variety of binder contents, binder compositions and WC grain sizes at temperatures ranging from 700 °C to 950 °C. The creep behaviour was characterised using compressive high-temperature experiments. The results show that the above mentioned microstructural parameters as well as the binder composition have a significant influence on the samples' plastic deformation. Based on these findings, a structured creep behaviour control map may be established for future materials development, aiding in the design of new high performing cemented carbides for challenging technical applications. Highlights: The high-temperature creep behaviour of cemented carbides was evaluated for a wide variety of binder contents at temperatures ranging from 700 °C to 950 °C. The high-temperature creep behaviour of cemented carbides was evaluated for a wide variety of binder compositions at temperatures ranging from 700 °C to 950 °C. The high-temperature creep behaviour of cemented carbides was evaluated for a wide variety of WC grain sizes at temperatures ranging from 700 °C to 950 °C.